1999
DOI: 10.1099/00221287-145-9-2615
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid transfer in the animal intestine and other dynamic bacterial populations: the role of community structure and environment

Abstract: The transfer of the R1drd19 plasmid between isogenic strains of Escherichia coli BJ4 in batch cultures of laboratory media and intestinal extracts was compared. Using an estimate of plasmid transfer rate that is independent of cell density, of donor :recipient ratios and of mating time, it was found that transfer occurs at a much lower rate in intestinal extracts than in laboratory media. Furthermore, the results suggest that the majority of intestinal plasmid transfer takes place in the viscous mucus layer co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
139
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(153 citation statements)
references
References 34 publications
(11 reference statements)
11
139
2
1
Order By: Relevance
“…Pinedo & Smets (2005) observed a dependence of plasmid transfer efficiency on the donor to recipient ratio in filter matings that is not captured by mass-action models. In another study (Licht et al, 1999), the dynamics of transconjugant formation in the mouse gut were shown to be quite similar to those in a laboratory-grown biofilm and different from those observed in a chemostat and expected from a mass-action model. In addition to these empirical results, it is now mathematically well established (Durrett & Levin, 1994b;Hanski & Gilpin, 1997;Tilman & Kareiva, 1997;Dieckmann et al, 2000;Wei & Krone, 2005) that ignoring spatial structure in biological systems can lead to inaccuracies that are sometimes dramatic.…”
Section: Introductionmentioning
confidence: 91%
“…Pinedo & Smets (2005) observed a dependence of plasmid transfer efficiency on the donor to recipient ratio in filter matings that is not captured by mass-action models. In another study (Licht et al, 1999), the dynamics of transconjugant formation in the mouse gut were shown to be quite similar to those in a laboratory-grown biofilm and different from those observed in a chemostat and expected from a mass-action model. In addition to these empirical results, it is now mathematically well established (Durrett & Levin, 1994b;Hanski & Gilpin, 1997;Tilman & Kareiva, 1997;Dieckmann et al, 2000;Wei & Krone, 2005) that ignoring spatial structure in biological systems can lead to inaccuracies that are sometimes dramatic.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, in complex bacterial ecosystems, low densities of donor and recipient bacteria may lower the frequency of direct bacterial encounters and thus decrease the chance of conjugation-mediated HGT. Several studies reported inefficient enterobacterial HGT in the normal mammalian gut (15)(16)(17), whereas others identified higher rates of HGT (18,19). This suggested that particular conditions exist that might favor plasmid exchange between Enterobacteriaceae.…”
mentioning
confidence: 94%
“…Conjugative plasmid transfer is no exception to this, as it requires cell contact and is therefore determined by the spatial configuration of a population or community. The failure of ordinary differential equation models to capture experimentally observed dynamics of plasmid transfer has already been demonstrated in several studies (Simonsen, 1990;Licht et al, 1999;Pinedo and Smets, 2005;Krone et al, 2007). Moreover, plasmids such as those of the IncP-1 group transfer at higher rates on solid substrates than in liquids.…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses have been raised about possible plasmid transfer inhibition mechanisms, or the lack of nutrient availability in those deeper cell layers. Nutrients have been shown to positively affect plasmid transfer efficiency in some cases, but not in others (Hausner and Wuertz, 1999;van Elsas and Bailey, 2002), and therefore it remains unclear why a plasmid does not completely invade a colony or biofilm, and if specific conditions may be conducive to plasmid invasion (Licht et al, 1999;Molin and Tolker-Nielsen, 2003).…”
Section: Introductionmentioning
confidence: 99%